2014
DOI: 10.3389/fnana.2014.00075
|View full text |Cite
|
Sign up to set email alerts
|

Conserved localization of Pax6 and Pax7 transcripts in the brain of representatives of sarcopterygian vertebrates during development supports homologous brain regionalization

Abstract: Many of the genes involved in brain patterning during development are highly conserved in vertebrates and similarities in their expression patterns help to recognize homologous cell types or brain regions. Among these genes, Pax6 and Pax7 are expressed in regionally restricted patterns in the brain and are essential for its development. In the present immunohistochemical study we analyzed the distribution of Pax6 and Pax7 cells in the brain of six representative species of tetrapods and lungfishes, the closest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 140 publications
5
13
0
Order By: Relevance
“…The antibody was subsequently purified on a Protein A column and is useful in studying brain, neuronal, and olfactory development in eukaryotes (see data sheet from Covance, Princeton, NJ). The western blot for the brain extract of Xenopus shows a band that corresponded well to those obtained in rat, turtle, and urodele lanes, and coincides with the calculated molecular weight (Moreno et al, ).…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The antibody was subsequently purified on a Protein A column and is useful in studying brain, neuronal, and olfactory development in eukaryotes (see data sheet from Covance, Princeton, NJ). The western blot for the brain extract of Xenopus shows a band that corresponded well to those obtained in rat, turtle, and urodele lanes, and coincides with the calculated molecular weight (Moreno et al, ).…”
Section: Methodssupporting
confidence: 82%
“…The specificity of the antibodies used has been assessed by the commercial suppliers (Table ); in addition, immunoblotting was conducted. The western blots of brain extracts of Xenopus laevis showed that all antibodies and sera used here labeled a single band, which with small variations corresponded well with the bands labeled in the rat lanes (Morona and González, ; Morona et al, ; Moreno et al, ).…”
Section: Methodssupporting
confidence: 73%
“…We detected adjacent expression of pax7a and bsx (Figures 2E-E ). Co-staining of bsx and pax6a, the latter having been described to be expressed in the alar part of prosomer 3 (p3a; Martinez-Ferre and Martinez, 2012; Moreno et al, 2014), also revealed adjacent expression domains (Figures 2D-D ) rather than overlapping ones. Co-staining pax6a and pax7a confirmed existence of a domain located right at both, the border between alar and basal plate, and the border between prosomer 3 and hypothalamus (Figures 2F-G , arrowheads in Figures 2F ,G).…”
Section: Bsx Is Expressed In Both Tuberal and Mamillary Regions Of Thmentioning
confidence: 84%
“…These two regions of the lungfish brain are virtually devoid of Pax6 cells in the adult, in agreement with results in amphibians (Bandín et al, ; Joven et al, ), turtles (Moreno, Domínguez, et al, ), and chickens (Abellan & Medina, ). In contrast, in mammals (mice), Pax6 has been described in the lateral portion of the preoptic area in adults (Duan et al, ), and the presence of Pax6 cells in the hypothalamic paraventricular region is a feature shared by amniotes (Medina, ; Moreno, Domínguez, et al, ) and not observed in anamniotes (Domínguez et al, ; Moreno et al, ; Moreno & González, ; Murakami et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, as neurodevelopment proceeds, the expression pattern of Pax6 changes from the mitotic germinal zone in the ventricular zone to become distributed in cell groups in the adult brain (Chalepakis, Stoykova, Wijnholds, Tremblay, & Gruss, ; Duan et al, ; Moreno et al, ; Stoykova & Gruss, ), suggesting that it may have a role in later development of the nervous system when neurons differentiate and develop synaptic connections. Actually, the functional implications of Pax6 in the brains of adult vertebrates have received substantially increasing attention after the discovery that this factor is involved in the processes of reparative neurogenesis in vertebrate animals and humans (Thompson & Ziman, ).…”
Section: Introductionmentioning
confidence: 99%